CHANGE OF POSITIONS OF THE CONDUCTION BAND MINIMA DEPENDING ON COMPOSITION OF SOLID SOLUTIONS - Vahanyan, A. I. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2007)
A formula allowing to define changes of positions of the basic minima in a zone of conductivity of solid solutions depending on the composition of the latter is obtained. The data analyzed by the derived formula are compared with data verified by other methods. The comparison yielded good data agreement.